(untitled) (Research, Society and Development, 2022)
Objective: To discuss the repercussions on the mental health of people living with chronic kidney disease in renal replacement therapies. Method: Integrative literature review. Data were obtained from the Higher Education Personnel Improvement (CAPES) database: Medical Literature and Retrivial System online (MEDLINE), Excerpta Medica Database (EMBASE), Scientific Electronic Library Online (SCIELO) and Cumulative Index to Nursing and Allied Health Literature (CINAHL), using the thesaurus: Chronic Renal Failure; Renal Dialysis; Mental Health. A time frame from 2015 to 2020 was determined for manuscript eligibility. After applying the inclusion and exclusion criteria, 10 articles were selected for the construction of this study. Results: It was found that the occurrence of depression in this population ranges from 27% to 100%; the rate of anxiety disorders ranged from 25.2%-35.5%; and the occurrence of hospitalization due to psychiatric problems in individuals with chronic kidney disease is significant, with a high rate of suicidal ideation ranging from 21.5% to 37% in those undergoing renal replacement therapy. Final Considerations: Given the impact on the mental health of people living with chronic kidney disease and renal replacement therapies, with segments such as depression, anxiety disorder, sleep disorder and suicidal ideation, it is necessary to develop innovative research focused on preventive measures mental health as well as in nursing care.